Elucidation of the Reinforcing Spleen Effect of Jujube Fruits Based on Metabolomics and Intestinal Flora Analysis - Yi, Yan-ling; Li, Yao; Guo, Sheng; Yan, Hui; Ma, Xin-fei; Tao, Wei-wei; Shang, Er-xin; Niu, Yang; Qian, Da-wei; Duan, Jin-ao (Frontiers in Cellular and Infection Microbiology, 2022)
Jujube (Ziziphus jujuba Mill.) fruit (JF) is widely consumed as food in Asian countries due to its potential effects for human health. As a traditional Chinese medicine, JF is often used to treat anorexia, fatigue and loose stools caused by spleen deficiency syndromes in China, but the mechanism underlying this effect has not been thoroughly elucidated. In this study, a rat model of spleen deficiency syndromes was adopted to investigate the therapeutic effect of JF extract and its possible mechanism by metabolomics analyses of plasma and urine as well as the intestinal flora analysis. The results showed that the changes in plasma and urine metabolites caused by spleen deficiency were reversed after administration of JF, and these changed endogenous metabolites were mainly involved in retinol metabolism, pentose and glucuronate interconversions, nicotinate and niacinamide metabolism pathways. The 16S rDNA sequencing results showed that JF could regulate intestinal flora imbalance caused by spleen deficiency. The covariance analysis of intestinal flora structure and metabolome indicated that Aerococcus may be a candidate strain for predicting and treating the metabolic pathways of spleen deficiency and related disorders. In summary, it can be revealed that spleen deficiency, which alters metabolic profiles and the intestinal flora, could be alleviated effectively by JF extract.